Source Identification of Carbonaceous Aerosols During Winter Months in the Dhaka City (Journal of Bangladesh Academy of Sciences, 2012)
Air particulate matter samples were collected using Air Metrics samplers from 11 - 17 January  and 19 - 27 January, 2012 at Amin Bazar and Farm Gate sites, respectively. The sampling time was  from 8 a.m. - 4 p.m. Three samplers were used of which two samplers were for PM2.5 samples,  using Teflon and quartz filters and the others for PM10 samples using Teflon filter. Organic and  elemental carbons (OC and EC) were measured in PM2.5 samples at both sites. It has been found  that the EC concentration at Amin Bazar is higher than in Farm Gate. The contribution of EC may  come from diesel, gasoline and coal/wood combustions in the Amin Bazar site. The present  OC/EC data were compared with the previous data. It was found that the concentration of EC became higher than those in the previous year. During last couple of years, Government   implemented different policies specially in case of motor vehicles to improve the air quality. But  due to the use of diesel in quick rental power plants, the air quality start to deteriorate. BC plays an  important role to change the climate. Hence, government should think of alternatives to meet the  power demand in place of diesel. DOI: http://dx.doi.org/10.3329/jbas.v36i2.12970 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 2, 241-250, 2012